Estimating the total incidence of type 1 diabetes in children and adolescents aged 0–19 years from 1990 to 2050: a global simulation-based analysis. Issue 12 (December 2022) - Ward, Zachary J; Yeh, Jennifer M; Reddy, Che L; Gomber, Apoorva; Ross, Carlo; Rittiphairoj, Thanitsara; Manne-Goehler, Jennifer; Abdalla, Asmahan T; Abdullah, Mohamed Ahmed; Ahmed, Abdurezak; Ankotche, Amos; Azad, Kishwar; et al.
Summary: Background: Previous studies of type 1 diabetes in childhood and adolescence have found large variations in reported incidence around the world. However, it is unclear whether these reported incidence levels are impacted by differences in country health systems and possible underdiagnosis and if so, to what degree. The aim of this study was to estimate both the total and diagnosed incidence of type 1 diabetes globally and to project childhood type 1 diabetes incidence indicators from 1990 to 2050 for each country. Methods: We developed the type 1 diabetes global microsimulation model to simulate the natural history and diagnosis of type 1 diabetes for children and adolescents (aged 0–19 years) in 200 countries and territories, accounting for variability in underlying incidence and health system performance. The model follows an open population of children and adolescents in monthly intervals and simulates type 1 diabetes incidence and progression, as well as health system factors which influence diagnosis. We calibrated the model to published data on type 1 diabetes incidence, autoantibody profiles, and proportion of cases diagnosed with diabetic ketoacidosis from 1990 to 2020 and assessed the predictive accuracy using a randomly sampled test set of data withheld from calibration. Findings: We estimate that in 2021 there were 355 900 (95% UI 334 200–377 300) total new cases of type 1 diabetes globally among children and adolescents, of which 56% (200 400 cases, 95% UI 180 600–219 500) were diagnosed. Estimated underdiagnosis varies substantially by region, with over 95% of new cases diagnosed in Australia and New Zealand, western and northern Europe, and North America, but less than 35% of new cases diagnosed in west Africa, south and southeastern Asia, and Melanesia. The total number of incident childhood cases of type 1 diabetes is projected to increase to 476 700 (95% UI 449 500–504 300) in 2050. Interpretation: Our research indicates that the total global incidence of childhood and adolescent type 1 diabetes is larger than previously estimated, with nearly one-in-two children currently undiagnosed. Policymakers should plan for adequate diagnostic and medical capacity to improve timely type 1 diabetes detection and treatment, particularly as incidence is projected to increase worldwide, with highest numbers of new cases in Africa. Funding: Novo Nordisk.